Microglial heterogeneity: influence of human 2D, 3D, and co-culture models on gene expression and immune function - Etebar, Fazeleh; White, Anthony R.; Quek, Hazel (Frontiers in Cellular Neuroscience, 2026)
Microglia, the resident immune cells of the central nervous system, exhibit substantial phenotypic and functional diversity shaped by local microenvironmental cues. While advanced in vitro human microglial models exist, the influence of culture dimensionality and cellular context on microglial state composition remains poorly defined. Here, we analyzed single-cell RNA sequencing datasets from human monocyte-derived microglia (MDMi) cultured under two-dimensional (2D) and three-dimensional (3D) monoculture, as well as 3D neural–glial co-culture conditions. Across platforms, four microglial states were identified, including interferon (IFN)-responsive, chemokine-enriched, metabolically active, and proliferative states, with pronounced environment-dependent transcriptional shifts. 2D cultures were dominated by IFN-responsive microglia characterized by elevated IFITM2 and IFITM3 expression, whereas 3D systems supported greater cellular diversity, including expanded metabolic programs and chemokine remodeling. Co-culture further increased proliferative microglia and induced immune-communication signatures involving CCL2/CCL5/CCL7, CSF1, and VEGF/FLT1 pathways. Pseudotime analysis revealed a largely linear trajectory in 2D cultures, but branching differentiation paths in 3D and co-culture systems, consistent with enhanced microglial heterogeneity. Benchmarking against human microglial reference signatures demonstrated broader and stronger overlap in 3D-based models, with homeostatic and disease-associated modules engaged in a context-specific manner. These findings demonstrate that culture architecture is a major determinant of microglial identity and immune responsiveness; and highlight the value of single-cell datasets to uncover previously underappreciated microglial states with relevance to human neuroimmune biology.